Uncommon gynecologic cancers - Del Carmen, Marcela; Schorge, John O.; Young, Robert H. (Robert Henry), 1950-; Birrer, Michael J. (Chichester, West Sussex ; Hoboken, NJ : John Wiley & Sons Inc., 2014)
Rare gynecological cancers kill all too commonly Gynecological cancer is a frightening prospect for women. It is terrifying also for physicians who need, but often can't find, guidance on how to investigate and appropriately treat the tumors. Rare cancers provide greater challenges as information can be harder to find and more difficult to verify. Rare Gynecologic Cancers: Diagnosis and Management brings together all you need to know on these life-threatening diseases. Straightforward summaries of pathophysiologic processes lead to the investigations that will improve your diagnostic accuracy.
Molecular targets in gynecologic cancers / Whitfield Growdon, Rosemary Foster, Bo Rueda -- Imaging of rare gynecologic tumors / Hima B. Prabhakar, Dinushi S. Perera -- Pathology overview of rare gynecologic tumors / Robert H. Young -- Ovarian clear cell carcinoma / Rachel M. Clark, John O. Schorge -- Mucinous epithelial ovarian carcinoma / Marcela G. del Carmen -- Pseudomyxoma peritonei / Leslie S. Bradford, Annekathryn Goodman -- Squamous cell carcinoma of the ovary / Ryan J. Spencer, Laurel W. Rice -- Endometriosis-associated ovarian cancer / Leslie A. Garrett, Marcela G. del Carmen -- Carcinosarcoma of the ovary / J. Alejandro Rauh-Hain, Marcela G. del Carmen -- Malignant germ cell tumors of the ovary / Marcela G. del Carmen -- Malignant sex cord-stromal tumors of the ovary / Marcela G. del Carmen, Richard T. Penson -- Small cell and neuroendocrine cancers of the ovary / Ariel A. Kaphan, Cesar M. Castro -- Carcinoid tumors of the ovary / Michael J. Worley, Michael G. Muto -- Uterine carcinosarcoma / Premal H. Thaker, Don S. Dizon -- Uterine leiomyosarcoma / Marcela G. del Carmen -- Mucinous tumors of the uterine corpus / Rachel M. Clark, Marcela G. del Carmen -- Uterine clear cell carcinoma / J. Alejandro Rauh-Hain, Alexander B. Olawaiye, David M. Boruta -- Updates in the management of uterine serous cancer / Amanda Ramos, Amanda Nickles-Fader -- Endometrial stromal sarcomas / Kathleen M. Schmeler, J. Alejandro Rauh-Hain, Marcela G. del Carmen -- Small cell and neuroendocrine cancers of the cervix / Olivia W. Foley, Leslie S. Bradford, Marcela G. del Carmen -- Primary malignant melanoma of the vagina and vulva / Alexander B. Olawaiye -- Sarcomas of the vulva and vagina / Rachel M. Clark, J. Alejandro Rauh-Hain, Marcela G. del Carmen -- Gestational trophoblastic disease / Whitfield Growdon.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Generative organs, Female -- Cancer -- Treatment; Genital Neoplasms, Female; Medical; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Generative organs, Female -- Cancer -- Treatment; Electronic books